1990
DOI: 10.1128/jb.172.11.6427-6434.1990
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactamase expression in Streptomyces cacaoi

Abstract: Plasmids were prepared by inserting genomic DNA fragments from Streptomyces cacaoi within the mel gene of plasmid pU.702. The inserted DNA fragments contain the i-lactamase-encoding bla gene and upstream nucleotide sequences of various lengths. The transcription start point of bla was identified by nuclease Si mapping. Upstream nucleotide sequences of sufficient lengths had an enhancing effect on I8-lactamase production by the Streptomyces host. The dot blot hybridization assay revealed that this effect was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…14 and 15 for the blaU upstream region. The sequences of the oligonucleotides 1 to 15 are given in C. The A10 and A35 promoter regions of blaL (Urabe et al 1990), blaA (Urabe and Ogawara 1992) and blaU (Forsman 1991) genes are shown, as well as the transcription starts and the ribosomebinding sites of blaL and blaU (rbs). For BlaA, the transcription start coincides with the translation start (Urabe and Ogawara 1992) (lanes 7, 8).…”
Section: A T-n 11 -A Motif Is Also Present Upstream Of Blaumentioning
confidence: 99%
“…14 and 15 for the blaU upstream region. The sequences of the oligonucleotides 1 to 15 are given in C. The A10 and A35 promoter regions of blaL (Urabe et al 1990), blaA (Urabe and Ogawara 1992) and blaU (Forsman 1991) genes are shown, as well as the transcription starts and the ribosomebinding sites of blaL and blaU (rbs). For BlaA, the transcription start coincides with the translation start (Urabe and Ogawara 1992) (lanes 7, 8).…”
Section: A T-n 11 -A Motif Is Also Present Upstream Of Blaumentioning
confidence: 99%
“…In previous studies, the gene encoding the P-lactamase of Streptomyces cacaoi (38) was cloned and sequenced (26,27). During these studies, we found that the upstream sequence of the structural gene had an enhancing effect on 3-lactamase production by a StreptomWces host, Streptomyces lividans (51). In addition, the same nucleotide sequence is necessary for the inducible expression of the S. cacaoi * Corresponding author.…”
mentioning
confidence: 99%
“…On the other hand we cannot exclude the influence of upstream regulatory sequences like those described by Urabe et al (1990) because the amplified promotercontaining DNA fragments are long enough to comprise such regions and the sequences 500 to 300 bp upstream of the start codon are diverse, so they may exert different influences on the downstream promoters. This influence would have to be caused by cis-acting elements, because we did not amplify the open reading frame situated upstream of the SHV-2a P-lactamase gene (1 135 to 899 nucleotides in front of the start codon; there is none in front of the SHV-2 gene).…”
Section: Discussionmentioning
confidence: 99%